Rocking the boat conserving fisheries and protecting jobs. - McGinn, A.P. (Washington Worldwatch Institute, 1998)
Worldwatch Pap. (142)
Keywords: Sustainable aquaculture; Resource management; Resource conservation; Fisheries; Fishery management